The features of the development of higher education in librarianship in Soviet Lithuania - Gudauskas, Renaldas (Knygotyra, 1988)
Attempts to organize higher library education in Lithuania were made long ago. An episodic course in bibliography was taught at the old Vilnius University in 1829-1830. After the restoration of Soviet power in Lithuania in 1940, the Chair of Bibliology was established at Vilnius State University, and a course in bibliography was offered. Lectures aimed at starting the preparation of skilled librarians and bibliographers were planned to begin in the autumn of 1941. However, this work was interrupted by the war and the Nazi occupation. The Department of Librarianship was founded at Vilnius State University in 1949 (with the Chair of Librarianship established in 1952, and the Chair of Scientific Information in 1973). During a short period, these Chairs achieved significant results in various branches. They developed scientific and research activity in librarianship and bibliography, providing skilled specialists for the libraries of our republic. In recent years, more than 2,000 specialists have been trained at the University. These graduates have been appointed to work in different public, children’s, school, scientific, special, and technical libraries, as well as in scientific information offices.